Images of synthetic life: Mapping the use and function of metaphors in the public discourse on synthetic biology - Braun, Matthias (PLoS One, 2018)
Synthetic biology is currently one of the most frequently addressed emerging biotechnologies. Developments within this field receive a great deal of attention in media coverage, in which they are frequently illustrated by certain forms of metaphorical speech. Although it can be assumed that societal perceptions and evaluations of emerging biotechnologies are shaped by media coverage and its transported images, there is a lack of empirical research examining the reporting on synthetic biology as well as the use and function of metaphors within media articles. Thus, filling in this gap is one of the urgent desiderata for gaining an enhanced understanding of public views and assessments of this field of biotechnology. Against this background, this article addresses two main questions: (1) Which metaphors and framings are prevalent in the media discourse and what meaning do they have? (2) In which way are metaphors used in media coverage and what function do they have? The research is based on a media content analysis and includes a total number of 11.867 German- as well as English-language media articles dealing with synthetic biology, covering the period between 2004 and 2015. The findings suggest that forms of metaphorical speech address the novelty of current and envisioned scientific developments, highlighting their potential to shift social values and cultural concepts of life and nature. Basic expressions for describing progress within the field of synthetic biology are mainly descriptive metaphors originating from the semantic fields of craft, engineering, IT or art. In comparison, the total frequency of religiously charged metaphors, such as “playing God” or “creating life”, is substantially lower. This low usage rate of religio-cultural expressions in media coverage can be considered a surprising result, since other empirical studies and particularly the ongoing broader ethical discussion attach more importance to these forms of metaphorical speech.